Soft Computing and Decision Support System for Software Process Improvement : A Systematic Literature Reviewlightweight mutual authentication methods for internet of things, so our concern should be Lightweight mutual authentication methods not the IOT. for IOT (scope of networks) we will choose later - He, Xiaolong; Zhao, Huiqi; Zhong, Lunchao; Shah, Nazir; Deng, Jun; Adnan, Shahid Khan (Hindawi, 2021)
Software project development is very crucial, and measuring the exact cost and effort of development is becoming tedious and challenging. Organizations are trying to wind up their project of software development within the agreed budget and schedule successfully. Traditional practices are inadequate to achieve the current needs of the software industry. Underestimation and overestimation of software development effort lead to financial implications in the form of resources, cost of staffing, and budget of developing the software project. Soft computing (SC) approaches and tools deliver an addition of techniques for anticipating resistance to the deception, defect, incomplete truth for traceability and ambiguity, low arrangement cost, and strength. A large amount of SC approaches is prevailing in the literature to accomplish way-out to difficulties precisely, practically, and speedily. .e approaches of SC can give better prediction, high performance, and dynamic behavior. SC deals with computational intelligence which integrates the concept of agent paradigm and SC. .e proposed study presents a systematic literature review (SLR) of the approaches, tools, and techniques of SC used in the literature. .e study presented a comprehensive review by searching the defined keywords in the popular libraries, filtered the paper, and obtained most relevant papers. After the selection of the papers, the quality assessment process of the included papers has been done in order to determine the relevancy of the papers. .e study will help researchers in the area of research to devise novel ideas and solutions to overcome the existing issue on the basis of this study as evidence of the literature.